MEDIAN LETHAL CONCENTRATION (LC-50) INSEKTISIDA DIKLOROMETAN PADA NENER BANDENG (Chanos-chanos Forks) - Rumampuk, Natalie D; Tilaar, Sandra; Wullur, Stenly (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
The result showed that the median of the lethal concentration (LC-50) of dichloromethane insecticides on nener milkfish (Chanos chanos Forsk) for 12 hours and 24 hours are 0.786 ppm, and 0.287 ppm, respectively. The increasing tendency of the time there is less lethalconcentration values, whereas the higher concentration, then the sooner the death of test organisms.